Impact of lymph node dissection on the prognosis of intrahepatic cholangiocarcinoma: a systematic review and meta-analysis - Yu, Jun; Zhou, Fan; Tan, Xing-Guo; Guo, Jun; Feng, Wei (Frontiers in Oncology, 2025)
BackgroundIntrahepatic cholangiocarcinoma (iCCA) is a malignant tumor second only to hepatocellular carcinoma in terms of incidence among primary liver cancers. Surgical resection is currently the preferred treatment for iCCA. However, the prognostic significance, complications, and clinical benefits of lymph node dissection (LND) in iCCA patients remain a topic of debate within the academic community.MethodsTo evaluate the impact of LND on overall survival (OS) and prognosis in patients with resectable iCCA, studies published from various databases, including PubMed, Embase, Web of Science, and the Cochrane Library. A meta-analysis was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The impact of LND on prognosis was analyzed.ResultsA total of 5,787 patients from twenty-one retrospective cohorts were included in the final analysis. The results indicated that clinically node-negative patients who underwent LND had significantly better survival outcomes compared to those who did not undergo LND (P<0.01). In the R0 resection subgroup, LND was associated with improved survival compared to non-LND (P<0.01), while in the non-R0 resection subgroup, the LND group exhibited significantly fewer survival benefits than the non-LND group (P<0.01). When Compared to patients in the non-LND group, those in the LND N- group demonstrated significantly greater survival (P<0.05), while patients in the LND N+ group experienced significantly shorter OS (P<0.01).ConclusionPatients with resectable iCCA who underwent LND had better survival outcomes compared to those who did not undergo LND. Therefore, routine LND should be performed for clinically lymph node-negative (cLNM-) iCCA patients.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024564741.